Modeling the Reliability Indicators' Kinetics of a Mobile Ropeway Formed by the Self-Propelled Units - Alexander Lagerev; Igor Lagerev (Communications - Scientific letters of the University of Zilina, 2022)
A promising type of cargo vehicles are mobile ropeways formed by autonomous self-propelled rope units connected by a common cable transport system. The article presents a method for predicting the kinetics of the reliability indicators of the ropeway as a whole, individual rope units and their subsystems, taking into account the timing and volume of planned repairs. This method is advisable to use at the design stage of rope units, as it allows one to simulate the stage of their operation and provide the required level of reliability based on proactive replacement of structural elements that have reached the maximum permissible probability of critical failure. The method makes it possible to solve a number of important technical and economic problems related to operation of units and ropeways, including the development of an optimal strategy for their planned repairs, which has a minimum cost.